28-(3c+4)=2(c+6)+c

Since c is on the right side of the equation, switch the sides so it is on the left side of the equation.

2(c+6)+c=28-(3c+4)

Simplify each term.

Apply the distributive property.

2c+2⋅6+c=28-(3c+4)

Multiply 2 by 6.

2c+12+c=28-(3c+4)

2c+12+c=28-(3c+4)

Add 2c and c.

3c+12=28-(3c+4)

3c+12=28-(3c+4)

Simplify each term.

Apply the distributive property.

3c+12=28-(3c)-1⋅4

Multiply 3 by -1.

3c+12=28-3c-1⋅4

Multiply -1 by 4.

3c+12=28-3c-4

3c+12=28-3c-4

Subtract 4 from 28.

3c+12=-3c+24

3c+12=-3c+24

Add 3c to both sides of the equation.

3c+12+3c=24

Add 3c and 3c.

6c+12=24

6c+12=24

Subtract 12 from both sides of the equation.

6c=24-12

Subtract 12 from 24.

6c=12

6c=12

Divide each term in 6c=12 by 6.

6c6=126

Cancel the common factor of 6.

Cancel the common factor.

6c6=126

Divide c by 1.

c=126

c=126

Divide 12 by 6.

c=2

c=2

Solve for c 28-(3c+4)=2(c+6)+c